2003
DOI: 10.1665/1082-6467(2003)012[0089:sospoa]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Schistocerca piceifrons (Orthoptera: Acrididae) to Metarhizium anisopliae var. acridum (Deuteromycotina: Hyphomycetes): laboratory and field trials

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 18 publications
0
13
0
1
Order By: Relevance
“…hypothesised that surfactants disrupt the insect gut epithelium, increasing permeability to bacterial toxins. Hernández‐Velázquez et al . reported that a Citroline–conidial formulation of M. anisopliae had been successful in controlling the Central American locust in Mexico, promoting a decline of up to 99% under field conditions at 13 days post‐application.…”
Section: Discussionmentioning
confidence: 99%
“…hypothesised that surfactants disrupt the insect gut epithelium, increasing permeability to bacterial toxins. Hernández‐Velázquez et al . reported that a Citroline–conidial formulation of M. anisopliae had been successful in controlling the Central American locust in Mexico, promoting a decline of up to 99% under field conditions at 13 days post‐application.…”
Section: Discussionmentioning
confidence: 99%
“…Also, oils have been proposed as useful carriers to suspend conidia for the control of insect pests (Prior et al, 1988;Lomer et al, 1992;Bateman et al, 1993) and tick control (Maranga et al, 2005). A Citroline-conidia formulation of M. anisopliae has been successfully used in Mexico for the control of the Central American locust, Schistocerca piceifrons Walker (Orthoptera: Acrididae), promoting up to 99% decline in field bands, 13 days after field application (Hernández-Velázquez et al, 2003). However, in the present study the Citroline formulation did not promote a significant reduction of tick larvae numbers; this could be attributed to several factors.…”
Section: Treatementsmentioning
confidence: 99%
“…However, in the present study the Citroline formulation did not promote a significant reduction of tick larvae numbers; this could be attributed to several factors. In particular, Citroline was used in combination with other carriers including water, as opposed to the formulae used by Hernández-Velázquez et al (2003) where Citroline was used as the sole component and applied as Ultra Low Volume (ULV). However, there is evidence suggesting that the grass species grown in a pasture bed along with weather conditions also affect the action of M. anisopliae to control R. microplus (Kaaya and Hassan, 2000;Basso et al, 2005).…”
Section: Treatementsmentioning
confidence: 99%
“…This culture was derived from the original MaPL40 strain, which has been successfully applied in field trials (Hernández-Velázquez et al 2003). Strain EH-502/8 was stored in a 10% glycerin solution in liquid nitrogen at -196°C.…”
Section: Spore Sourcementioning
confidence: 99%
“…Numerous studies have focused on the assessment of the virulence of various isolates of this fungus, as well as the feasibility of its use as a microbial agent (Hernández-Velázquez et al 2003;Hunter et al 2005). As a result, the commercial pesticide Green Muscle Ò has been developed, which has proven to be effective in controlling the desert locust (Schistocerca gregaria) and red locust (Nomadacris septemfasciata) and several species of African grasshoppers (Aston 2004;Kooyman et al 2003).…”
Section: Introductionmentioning
confidence: 99%